2006
DOI: 10.1086/505518
|View full text |Cite
|
Sign up to set email alerts
|

RHESSIObservations of the Solar Flare Iron‐Line Feature at 6.7 keV

Abstract: Analysis of RHESSI 3-10 keV spectra for 27 solar flares is reported. This energy range includes thermal free-free and free-bound continua and two line features, at $6.7 and $8 keV, principally due to highly ionized iron (Fe). We used the continuum and the flux in the so-called Fe-line feature at $6.7 keV to derive the electron temperature T e , the emission measure, and the Fe-line equivalent width as functions of time in each flare. The Fe/H abundance ratio in each flare is derived from the Fe-line equivalent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 22 publications
2
51
0
Order By: Relevance
“…We analysed the output from a single RHESSI detector 4F only because of its fine energy resolution of 0.98 keV (Smith et al 2002). Also, it produces a photon spectrum close to the mean spectrum of all front detectors usable for spectroscopy (Phillips et al 2006). Moreover, the drm_mod function can only be used to fit single-detector spectra.…”
Section: Rhessimentioning
confidence: 99%
“…We analysed the output from a single RHESSI detector 4F only because of its fine energy resolution of 0.98 keV (Smith et al 2002). Also, it produces a photon spectrum close to the mean spectrum of all front detectors usable for spectroscopy (Phillips et al 2006). Moreover, the drm_mod function can only be used to fit single-detector spectra.…”
Section: Rhessimentioning
confidence: 99%
“…The thermal plasma emission was modeled with an isothermal component (describing the free-free and free-bound continuum) and one Gaussian function to fit the 6.7 keV Fe line feature (method described in detail by Phillips et al 2006). The observed high-energy emission ( > ∼ 10 keV) was modeled as a nonthermal component with a power-law distribution I(E) ∝ E −γ , where γ represents the power-law index of the photon flux spectrum.…”
Section: September 13 (Event 1: On-disk)mentioning
confidence: 99%
“…Also, analysis of broad-band data from the RHESSI instrument in its A0 attenuator state (Phillips et al 2006) similarly indicates that there is a non-flaring component of emission, with temperature corresponding to the active region, as well as a hotter flare component.…”
Section: Observationsmentioning
confidence: 94%
“…It is assumed, as was found from the RESIK flare observations of Ar xvii line ratios (Sylwester et al 2008) and analysis of broad-band spectra from RHESSI in its A0 attenuator state (Phillips et al 2006), that a two-component emission measure distribution describes the observed spectra, a low-temperature component (1-4 MK) appropriate for the Na x and Ne ix emission from the non-flaring active region and The Na x lines were included in the synthesis program from the Aggarwal et al (2009) atomic data (Sect. 3.3) and the Na ix satellites, both those excited by dielectronic recombination and those formed by inner-shell excitation, from the data discussed in Sect.…”
Section: Synthetic Spectramentioning
confidence: 99%